Clinicopathological and molecular characteristics of endometrial neuroendocrine carcinomas reveal preexisting endometrial carcinoma origin. Issue 8 (20th May 2021) - Ono, Kyoko; Kasajima, Rika; Katayama, Kayoko; Miyagi, Yohei; Yokose, Tomoyuki
Abstract: Endometrial neuroendocrine carcinoma is a rare disease with unknown clinicopathological and molecular characteristics. Therefore, we conducted the present study to elucidate the clinicopathological and molecular characteristics of endometrial neuroendocrine carcinoma, as compared to conventional endometrial carcinoma, and to determine the origin of the former. We analyzed 22 endometrial neuroendocrine carcinomas and 22 conventional endometrial neoplasia cases with respect to clinical, histological and genetic features. Of these, 21/22 neuroendocrine carcinoma cases were admixed carcinomas, with 15 admixed with endometrioid adenocarcinoma. Genetic analysis of hotspot mutations in 50 cancer‐related genes revealed that the neuroendocrine carcinoma group carried mutations in PIK3CA (12/22 cases; 54%) and PTEN (8/22 cases; 36%), commonly encountered in endometrioid adenocarcinoma. Comparative statistical analysis of neuroendocrine carcinoma and conventional endometrial neoplasia cases showed a significant trend only in PIK3CA mutation. Moreover, in six mixed‐type neuroendocrine carcinoma cases, macrodissection was used to separate the neuroendocrine carcinoma and endometrioid adenocarcinoma components for next‐generation sequencing, which revealed several mutations common among the two. These findings suggest that endometrial neuroendocrine carcinoma could originate from conventional endometrial neoplasia, especially endometrioid adenocarcinoma.